Anticancer effect of Polyphyllin Ι in colorectal cancer cells through ROS-dependent autophagy and G2/M arrest mechanisms. Issue 12 (18th June 2018) - Yu, Si; Wang, Lijiao; Cao, Zhixing; Gong, Daoyin; Liang, Qianyi; Chen, Hanting; Fu, Huizhu; Wang, Wenwen; Tang, Xue; Xie, Zihao; He, Yang; Peng, Cheng; et al.
Abstract: Polyphyllin Ι is a steroidal saponin isolated from the rhizoma of Paris polyphylla . In the present study, we aimed to investigate the anticancer effects of polyphyllin Ι in colorectal cancer and to elucidate the potential underlying molecular mechanisms. Using, CCK8 assay, flow cytometry, laser confocal microscope analysis and western blot, the anticancer effects of the polyphyllin Ι were analysed in colorectal cells. Our results indicate that polyphyllin Ι significantly decreased cell viability of HCT 116 cells and induced autophagy. Furthermore, we found that polyphyllin Ι induced autophagy in an ROS-dependent cell death and not related with PI3 K/AKT/mTOR pathway. We also provide evidence that excessive ROS triggered by polyphyllin Ι could induce G2/M phase arrest via regulating cycle proteins expression of cell cycle regulators, such as p21 and cyclinB1. In conclusion, polyphyllin Ι exhibit anticancer effect through ROS-dependent autophagy and induces G2/M arrest in colorectal cancer. Abstract :